MICROSERVER PERFORMANCE ANALYSIS FOR HANDLING TRAFFIC AS A DEDICATED SERVER IN LOCAL NETWORKS - Stefanus Eko Prasetyo; Gusti Irawan (Universitas Internasional Batam, 2022)
Currently, many agencies or companies use computers to work in the office. MicroServer is a tiny piece of hardware to help smooth system operations. MicroServer has an essential function in computers, to limit local networks and internet networks. Proliant HPE is an alternative MicroServer to use servers easily and quickly. In this analysis design, the author uses a descriptive qualitative analysis research method in which the author sees and tests the speed of data transfer on a ProLiant HPE microserver. As for the analysis results, the author has the ambition to create a backup plan if he feels the network and cloud server is unsafe to focus on physical products such as servers or microservers. The resulting speed is considered feasible enough if using a local/internal network using a LAN, as for testing with servers and microservers,